2021
DOI: 10.1136/ijgc-2021-003014
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus-independent cervical cancer

Abstract: Cervical cancer is the fourth most frequent cancer in women worldwide, representing nearly 8% of all female cancer deaths every year. The majority of cases of cervical cancer are caused by human papillomavirus (HPV); however, up to 5% of tumors are not associated with HPV-persistent infection and, moreover, the new WHO Female Genital Tumors classification subdivided cervical squamous and adenocarcinomas into HPV-associated and HPV-independent tumors. Based on this new information, the aim of this review is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 63 publications
1
42
0
2
Order By: Relevance
“…We would like to congratulate Dr Fernandes and colleagues on their excellent and thorough review of human papillomavirus (HPV)-independent cervical cancer. 1 While the majority of cervical cancers have been shown to be caused by HPV, several studies have reported HPV-independent disease. It is thought that these tumors are more often associated with lymph node involvement in early stages, more distant metastases, and worse prognosis.…”
mentioning
confidence: 99%
“…We would like to congratulate Dr Fernandes and colleagues on their excellent and thorough review of human papillomavirus (HPV)-independent cervical cancer. 1 While the majority of cervical cancers have been shown to be caused by HPV, several studies have reported HPV-independent disease. It is thought that these tumors are more often associated with lymph node involvement in early stages, more distant metastases, and worse prognosis.…”
mentioning
confidence: 99%
“…The authors of the review on human papillomavirus (HPV)-independent cervical cancer1 cited our recent publication on HPV-negative squamous precursor lesions2 as support for the ‘hit-and-run theory’ of primarily HPV-driven precancers that—during cancer progression—lose HPV-oncogene expression 3. Our data, however, were misinterpreted.…”
mentioning
confidence: 83%
“…With increasingly improved HPV detection methods, a gradual decrease in the rate of HPV-negative samples was noted between 1990 and 2010 2. However, despite the development of highly sensitive tests for molecular detection of HPV in recent years, a small proportion of cervical cancer cases are consistently negative for HPV in almost all studies 3 4…”
Section: Introductionmentioning
confidence: 99%
“…According to recently published data and a 2017 meta-analysis that included 17 studies about HPV-negative cervical cancer worldwide, HPV-negative cervical cancer was considered a distinct subgroup that showed poor prognosis, and its mechanism of action still remains unclear 6 7. Researches have demonstrated that HPV-negative cervical cancer is more frequently associated with lympho-vascular invasion, lymph node metastasis, and local or distant recurrence than HPV-positive cervical cancer 4 8. Therefore, in 2020, the fifth WHO classification of female genital tumors officially divided cervical cancer into HPV-associated and HPV-independent tumors according to the HPV status 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation